Svetik a family memoir of Sviatoslav Richter - Moskalew, Walter 1937-; Moskalewa-Richter, Anna 1892-1963; Reincke, Dagmar von 1898-1984 (Toccata Press, 2015)
For well over half a century, since the Soviet regime first allowed Sviatoslav Richter to travel to the west, his name has been synonymous with the very pinnacle of pianistic art. His recorded legacy, extending from 1947 to 1994 is one of the largest and most admired ever assembled by any musician anywhere. Yet this prodigiously gifted artist underwent no formal musical studies of any kind until at the age of 22 when he left the relative obscurity of the Ukraine to seek the advice of Russia's most celebrated piano pedagogue, Heinrich Neuhaus, in Moscow. Neuhaus' astonished reaction to his first encounter with Richter, and his declaration that 'to teach one who already knows will only do damage', have passed into legend. Richter, a famously reclusive man outside a small circle of trusted companions, resisted speaking or writing about himself. As a result, comparatively little is known about his life before his move to Moscow. This lavishly illustrated book provides unique insights into the childhood and formative years of 'Svetik' - 'Little Light', as he was always known within the large and unusually creative family circle - in a provincial Ukrainian city during the traumatic years of revolution, civil war, famine and wartime occupation by German and Romanian forces. Walter Moskalew, Richter's much younger cousin, is guardian of a rich collection of photographs, reminiscences, drawings and letters of family members, notably the memoirs of Richter's mother Anna and his twenty-year-long correspondence with his beloved Aunt Meri. Walter Moskalew has collaborated with editor and translator Anthony Phillips to produce an indispensable account of the influences that shaped the artistry and world-view of the phenomenon that was Sviatoslav Richter.